The Formation, Detriment and Solution of Residual Lithium Compounds on Ni-Rich Layered Oxides in Lithium-Ion Batteries - Chen, Anqi; Wang, Kun; Li, Jiaojiao; Mao, Qinzhong; Xiao, Zhen; Zhu, Dongmin; Wang, Guoguang; Liao, Peng; He, Jiarui; You, Ya; Xia, Yang (Frontiers in Energy Research, 2020)
Ni-rich layered transition-metal oxides with high specific capacity and energy density are regarded as one of the most promising cathode materials for next generation lithium-ion batteries. However, the notorious surface impurities and high air sensitivity of Ni-rich layered oxides remain great challenges for its large-scale application. In this respect, surface impurities are mainly derived from excessive Li addition to reduce the Li/Ni mixing degree and to compensate for the Li volatilization during sintering. Owing to the high sensitivity to moisture and CO2 in ambient air, the Ni-rich layered oxides are prone to form residual lithium compounds (e.g. LiOH and Li2CO3) on the surface, subsequently engendering the detrimental subsurface phase transformation. Consequently, Ni-rich layered oxides often have inferior storage and processing performance. More seriously, the residual lithium compounds increase the cell polarization, as well as aggravate battery swelling during long-term cycling. This review focuses on the origin and evolution of residual lithium compounds. Moreover, the negative effects of residual lithium compounds on storage performance, processing performance and electrochemical performance are discussed in detail. Finally, the feasible solutions and future prospects on how to reduce or even eliminate residual lithium compounds are proposed.